The Parnaso School – Contributions for a Reflection - Resende, Joana de Magalhães (2018)
The object of this work is an existing Pedagogical Project in Oporto city (1958-2009): the Parnaso School and his creator, the composer Fernando Corrêa de Oliveira. Building on a compilation of primary sources from the Parnaso Archive and on the direct contact with alumni (students and teachers), we try to reconstruct the history of the Parnaso School, as well as of the Parnaso Building, shelter to innumerable cultural initiatives in the city of Porto. Close to 50 years later, we reflect on the viability of applying, in present days, Fernando Corrêa de Oliveira’s pedagogical principles.